lnfective endocarditis of the tricuspid valve - Marques, Cristina (1999)
A case of tricuspid valve infective endocarditis is described in a thirty-year-old man, without known cardiac pathology and no history of IV drug use. A polymicrobial spectrum was found and a large vegetation was seen on cardiac ultrasound. A review of the literature is presented concerning isolated tricuspid valve infective endocarditis with special reference to the possible predisposing factors.